Assessment Of Road Traffic Noise At Residential Area In Nibong Tebal, Pulau Pinang - Abdul Hamid, Nur Fatin Najiyah (Universiti Sains Malaysia, 2018)
This study focuses on the measuring noise levels at two residential areas in Nibong Tebal, Penang. The residential areas are low density residential areas (Kampung Batu 2 Jalan Sempadan, Kampung Sungai Bakau and Kampung Simpang Tiga) and medium density residential areas (Taman Sri Acheh, Taman Pekaka and Taman Ilmu Indah). The sound level meter is used to record noise levels for 15 minutes for each residential area and is repeated for two days on weekdays and weekends. The noise level measurements were monitored in the morning (0800-0930), evening (1400-1530) and night (2200-2330). The traffic density was manually counted simultaneously with noise level measurement. The measurement speed of vehicles were also recorded simultaneously to obtain the average speed of each type of vehicle according to Arahan Teknik Jalan (8/86), A Guide on Geometric Design of Roads (cars, light vans, motorcycle, small lorries and heavy lorries) by using speed laser gun. The average sound level (LAeq) obtained at the medium density residential areas ranges from 61.8 dB (A) to 69 dB (A) while for low density residential areas ranges from 54.9 dB (A) to 66.2 dB (A ). All the sound level (LAeq) recorded were exceeded the maximum permissible sound level (LAeq) according to the Planning Guidelines for Receiving Land Use for Planning and New Development for Environmental Noise Limits and Control by the Department of Environment.